Celebrity worship dan Impulsive buying pada Penggemar KPOP Idol - Asrie, Nadine Denita; Misrawati, Dian (Journal of Psychological Perspective, 2020)
This study aimed to determined and explained the impact of celebrity worship on impulsive buying of idol merchandise, in this study specifically on BTS merchandise. A sample of 303 respondents were teenagers aged 13 – 21 years who loved the idol group, BTS. The sampling technique uses a snowball-sampling technique. The measuring instrument used is The Impulse Buying Tendency which has been modified with the Cronbach alpha reliability coefficient of 0.862 and the Celebrity Attitude Scale which has been modified with the Cronbach alpha reliability coefficient of 0.901. The result showed that celebrity worship had an effect on impulsive buying on BTS merchandise with an R2 value of 0.278. The results of the study that celebrity worship has an effect on impulsive buying on BTS merchandise can be seen from the t count of 10.765 more than 1.967 with a significance value p less than 0.005. The conclusion is celebrity worship has an impact on impulsive buying on BTS merchandise for teenagers who are fans of BTS. Further research can be carried out on random idol groups other than BTS, so it can be seen whether celebrity worship really affects impulsive buying of idol merchandise in general.Abstrak. Penelitian ini bertujuan untuk mengetahui dan menjelaskan pengaruh celebrity worship terhadap impulsive buying pada merchandise idola, dalam penelitian ini khususnya merchandise BTS. Sampel sebanyak 303 responden merupakan remaja dengan rentang usia 12 – 20 tahun yang menggemari grup idola BTS. Teknik pengambilan sampel menggunakan teknik snowball-sampling. Alat ukur yang digunakan adalah The Impulse Buying Tendency yang telah dimodifikasi dengan koefisien reliabilitas cronbach alpha sebesar 0,862 dan Celebrity Attitude Scale yang dimodifikasi dengan koefisien reliabilitas cronbach alpha sebesar 0,901. Hasil penelitian menunjukan bahwa celebrity worship berpengaruh terhadap impulsive buying pada merchandise idola dengan nilai R2 sebesar 0,278. Hasil penelitian bahwa celebrity worship berpengaruh terhadap impulsive buying pada merchandise idola dapat dilihat dari t hitung sebesar 10,765 lebih dari 1,967 dengan nilai signifikansi p kurang dari 0,005. Dengan demikian dapat disimpulkan bahwa celebrity worship memiliki pengaruh terhadap impulsive buying merchandise BTS pada remaja penggemar grup idola BTS. Penelitian selanjutnya dapat dilakukan pada random grup idola lain selain BTS, sehingga dapat dilihat apakah celebrity worship benar mempengaruhi impulsive buying terhadap merchandise idola secara umum.